Removal of Methyl Orange from Aqueous Solution by Adsorption onto a Hydrogel Composite. Issue 2 (February 2018) - Tang, Yaoji; Yang, Rui; Ma, Dong; Zhou, Bin; Zhu, Linhui; Yang, Jing
Poly(acrylic acid- co -2-acrylamide-2-methyl-1-propanesulfonic acid)/kaolin hydrogel composite was synthesised using acrylic acid (AA), 2-acrylamide-2-methyl-1-propanesulfonic acid (AMPS) and kaolin (KL) as main materials. The composite was characterised and used to remove methyl orange (MO) from aqueous solutions. Effect of adsorption conditions, including initial concentration of MO, contact time, pH values and ionic strength, on the adsorption capacities was studied. Maximal adsorption capacity was 506 mg/g as the initial concentration of MO was 1000 mg/L. It showed that the adsorption process was spontaneous, and the isotherms and kinetics were in good agreement with the Freundlich isotherm model and pseudo-second-order equation, respectively.